Farmers' Perceptions on the Performance of Agricultural Extension in the Sustainable Urban Farming (P2L) Program in Yogyakarta City - Yunanto Yunanto; Retno Wulandari (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2024)
Using urban yard land for agriculture plays a crucial role in meeting family food needs and increasing household income. Agricultural extension workers play a significant role in supporting this initiative through the Sustainable Urban Farming (P2L) program in Yogyakarta City. They assist farmer groups in planning, implementation, monitoring, evaluation, and reporting to achieve the program's objectives. This study aims to evaluate the implementation of the P2L program, assess farmers' perceptions of the performance of agricultural extension workers, and identify the factors influencing these perceptions. 11 farmer groups in Yogyakarta, comprising 88 respondents, participated in this study. Perceptions were measured using a Likert scale, and the related factors were analyzed using Spearman's Rank Correlation. The results indicate that the P2L program has successfully improved food availability, accessibility, and household income through market-oriented food production. Farmers rated the performance of agricultural extension workers as good, with a total score of 260.42. However, factors such as age, non-formal education, farmers' knowledge, farming experience, and the use of Information and Communication Technology (ICT), showed only a very weak correlation with the performance of agricultural extension workers in planning, implementation, monitoring, evaluation, and reporting.